Effects on communication due to face mask use: an integrative review - Jonathan Grassi; Isabel Barreto de Oliveira; Laura Franco Chiriboga; Andréa Alves Maia; Margareth Attianezi; Aline Neves Pessoa Almeida (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to integrate evidence from studies on auditory perceptual and speech production effects in communication situations with face mask use. Methods: an integrative literature review, in MEDLINE, Cochrane Library and Embase databases. The guiding question was: what effects on communication (perceptual-auditory and speech production) occur with face mask use? Results: searches in electronic databases resulted in 1,478 studies and filtering resulted in 29 final studies. Conclusions: mask use has effects on communication, both in perception and speech production, factors that are also related to quality of life, stress and socio-emotional factors. These data can impact on indicators and alerts in favor of adopting strategies to manage mask use, involving speech production and perception when wearing a mask in health services.